Extended adjuvant endocrine therapy for women with hormone receptor-positive early breast cancer: A meta-analysis with trial sequential analysis of randomized controlled trials - Xie, Ming; Zhong, Yan; Yang, Yide; Shen, Fang; Nie, Yue (Frontiers in Oncology, 2022)
Abstract Objectives: The aim of the current study is to explore the association between extended adjuvant endocrine treatment and prognosis of women with hormone receptor-positive (HR+) early breast cancer. Methods: Databases including PubMed, Web of Science, Embase and the Cochrane Library databases were electronically searched to identify randomized controlled trials (RCTs) that reported extended endocrine therapy for women with HR+ early breast cancer. The retrieval time was limited from inception to September 2022. Two reviewers independently screened literature, extracted data, and assessed risk bias of included studies. Meta-analysis was performed by using R software Version 4.1.2 and STATA Version 12.0. Results: A total of 15 RCTs involving 29497 cases were included. The overall analysis showed that compared with the control, extended adjuvant endocrine therapy increased disease-free survival (DFS) (HR=0.814, 95% CI: 0.720-0.922, 95% PI: 0.556-1.194), overall survival (OS) (HR=0.885, 95% CI: 0.822-0.953, 95% PI: 0.771-1.035), relapse-free survival (RFS) (HR=0.833, 95% CI: 0.747-0.927, 95% PI: 0.575-1.159), distant metastatic-free survival (DMFS) (HR=0.824, 95% CI: 0.694-0.979, 95% PI: 0.300-2.089) and reduced new breast cancer cumulative incidence (NBCCI) (HR=0.484, 95% CI: 0.403-0.583, 95% PI: 0.359-0.654). For adverse events, extended adjuvant endocrine treatment was associated with a significantly higher risk of bone fracture (RR=1.446, 95% CI: 1.208-1.730, 95% PI: 1.154-1.854) and osteoporosis (RR=1.377, 95% CI: 1.018-1.862, 95% PI: 0.347-5.456). Conclusion: Our study showed that extended adjuvant endocrine therapy increased DFS, OS, RFS, DMFS, the incidence of bone fracture and osteoporosis, and reduced NBCCI.